Interpassivity and Presence: Some Reflections on the Concept of Autoteatro - Abuín González, Anxo (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2024)
As an exercise in immersive theatre, autoteatro, as developed by Ant Hampton (in collaboration with Silvia Mercuriali and Tim Etchells), is a type of theatre that relies on the participation of the spectator in dialogue with scripted materials. The concept also serves as a way of reconsidering the excesses of a ubiquitous interactive theatre that aims to blur the distinction between presence and absence, inside and outside, reality and imagination, art and the everyday. This “experience machine” puts all its gears in motion to create an automated and interpassive mechanism that transforms the body of the spectator into a sensorial and haptic space, a space of listening in which a kind of “delegated” pleasure allows for experience to be, in a sense, externalized, given over to an outside agency.